Discursive analysis of image realized on the empirical material (Methods of communication and media researches. Theoretical and analytical perspective, 2021)
The method of discursive image analysis realized on the empirical material was presented in this chapter. It is AN authorial method of image research which combines social sciences research methods with linguistics methodological solutions. This chapter presents the aim of the method, the range of research subjects, material, elements of research procedure, analytical tools, capabilities and limitations of the method.